Karakterisasi Aktivitas Antioksidan dan Antikolesterol Ekstrak Daun Beringin (Ficus benjamina L.) - Amelia Putri; Danang Raharjo (Jurnal Kesehatan Amanah, 2026)
This study aimed to characterize the antioxidant and anticholesterol activities of ethanol extract of banyan leaves (Ficus benjamina L.) in vitro. Hypercholesterolemia is closely associated with oxidative stress, particularly LDL oxidation, which contributes to atherosclerosis. Ethanol extraction was performed using maceration method with 96% ethanol. Antioxidant activity was evaluated using the ABTS radical scavenging method, while anticholesterol activity was determined using the Liebermann–Burchard method measured by UV-Vis spectrophotometry. The ethanol extract demonstrated strong antioxidant activity based on IC₅₀ value and showed significant cholesterol reduction activity in a concentration-dependent manner. The findings indicate that the ethanol extract of Ficus benjamina L. leaves possesses promising bioactivity as a natural antioxidant and anticholesterol agent. These activities are likely associated with the presence of phenolic and flavonoid compounds. The study supports the potential development of standardized herbal preparations from banyan leaf extract.